Pelatihan dan Pendampingan Inovasi Produk Unggulan dan Pemasaran On-Line - Djajanto, Ludfi; Kusmintarti, Anik; Wakhidah, Rokhimatul; Amerieska, Siti; Ismanu, Sidik (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2021)
Micro, Small and Medium Enterprises (MSMEs) play a very important role in supporting the improvement of the economy of Wringinsongo village, Malang Regency. MSME production of papaya chips and MSME of production of jemblem are currently the leading products in Wringinsongo village and have very good prospects. The main problems that are faced by the business development of MSME papaya chips production and MSME jemblem production are the production process is very simple, there is no product development or diversification, the number of product turnover is limited and the quality is not guaranteed, and the condition of the equipment is very simple and not feasible. In addition, only one type of product is produced and made according to their own tastes and there is no good packaging so that they are less attractive to consumers. The solutions to the problem solving carried out in this community service are by providing training and assistance on how to innovate products and diversify products, provide assistance with machines and equipment that support the production process, train how to design several packaging models, labeling, and brands for the product to be produced to make it more attractive, and train the development of effective sales and promotions through online marketing through several social media such as Instagram and Facebook. The results after training and mentoring show that there is an additional variety of product types and packaging that can directly increase sales turnover.